2016
DOI: 10.3847/2041-8205/826/1/l13
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Broadband Follow-Up of the Gravitational-Wave Transient Gw150914

Abstract: A gravitational-wave (GW) transient was identified in data recorded by the Advanced Laser Interferometer Gravitational-wave Observatory (LIGO) detectors on 2015 September 14. The event, initially designated G184098 and later given the name GW150914, is described in detail elsewhere. By prior arrangement, preliminary estimates of the time, significance, and sky location of the event were shared with 63 teams of observers covering radio, optical, near-infrared, X-ray, and gamma-ray wavelengths with ground-and sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
150
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 248 publications
(158 citation statements)
references
References 46 publications
4
150
0
4
Order By: Relevance
“…VI. The absolute time of detectors' data streams is accurate to within 10 μs, which does not limit the uncertainty in sky-location parameters for GW150914 [31,34]. Further, the phase uncertainty of the response function as shown in Sec.…”
Section: Impact Of Calibration Uncertainties On Gw150914mentioning
confidence: 97%
“…VI. The absolute time of detectors' data streams is accurate to within 10 μs, which does not limit the uncertainty in sky-location parameters for GW150914 [31,34]. Further, the phase uncertainty of the response function as shown in Sec.…”
Section: Impact Of Calibration Uncertainties On Gw150914mentioning
confidence: 97%
“…Despite the expectation that stellar mass BBH mergers do not produce electromagnetic signals, there was broadband follow-up of GW150914 [13]. This demonstrated the willingness of the wider astronomical community to engage in multimessenger observation of GW sources.…”
Section: Introductionmentioning
confidence: 99%
“…GRBs are believed to be sources of ultra-high energy cosmic rays (UHECR) (Waxman 2006;Abu-Zayyad et al 2012;Tokuno et al 2012;Abraham et al 2004;Panasyuk et al 2012;Takahashi 2009;Halzen and Klein 2010;Gorham et al 2009) and gravitational waves (GW) whose detection has been reported recently (Cutler and Thorne 2002;Abramovici et al 1992;Abbott et al 2016a), and is a prime example of multi-messenger astronomy. The rapid-response in the observation of electromagnetic counterparts to GW (Abbott et al 2016b) is important to obtain the rich information in physical processes of GRBs giving rise to each messenger and the time delay between them.…”
Section: Introductionmentioning
confidence: 99%